Immunodeficiencies (2009)
ABSTRACT: Primary immunodeficiencies (PIDs) are uncommon, chronic and severe disorders of the immune system in which patients cannot mount a sufficiently protective immune response, leading to an increased susceptibility to infections. The treatment of choice for PID patients with predominant antibody deficiency is intravenous immunoglobulin (Ig) replacement therapy. Despite major advances over the last 20 years in the molecular characterization of PIDs, many patients remain undiagnosed or are diagnosed too late, with severe consequences. Various strategies to ensure timely diagnosis of PIDs are in place, and novel approaches are being developed. In recent years, several patient registries have been established. Such registries shed light on the pathology and natural history of these varied disorders. Analyses of the registry data may also reveal which patients are likely to respond well to higher Ig infusion rates and may help to determine the optimal dosing of Ig products. Faster infusion rates may lead to improved convenience for patients and thus increase patient compliance, and may reduce nursing time and the need for hospital resources. Data from two recent studies suggest that Gamunex® and Privigen® are well tolerated at high infusion rates. Nevertheless, careful selection of patients for high infusion rates, based on co-morbid conditions and tolerance of the current infusion rate, is advisable. Based on the available data, intravenous Ig offers broad protection against encapsulated organisms. As vaccine trends change, careful monitoring of specific antibody levels in the general population, such as those against pneumococcal and meningococcal bacteria, should be implemented.